Studying the Correlation between Dignity and Functional Independence in the Elderly in Tehran in 2020 - Goodarzi, Elnaz; Esmaeili, Roghayeh; Boozari Pour, Mahsa (Advances in Nursing & Midwifery, 2023)
Abstract Introduction: As the elderly population continues to grow, numerous challenges were faced in enhancing their quality of life. Maintaining dignity and functional independence are crucial factors during this stage of life. This study was conducted to determine the correlation between dignity and functional independence during the elderly period. Methods: A descriptive-correlational study was conducted, involving 263 elderly residents from four regions of Tehran, using a multi-stage stratified sampling approach. The study utilized daily activity questionnaires, instrumental activities of daily living questionnaires, and elderly dignity questionnaires using a 5-point Likert scale, demographic questionnaires and cognitive screening tests for data collection. Descriptive and analytical statistical tests, such as the Pearson correlation coefficient and multiple linear regression using SPSS21 software, were used for data analysis. Results: The participants' average age was 68.4 ± 2.7 years, and the majority (71.9%) reported a moderate level of dignity. Only 26.6% were fully independent in performing daily activities, and 17.5% were fully independent in instrumental activities. The results have confirmed the significant impact of functional independence and health on the dignity of older adults (P<0.001). Furthermore, the multivariate regression results showed that healthy elderly individuals had an average dignity score 4.39% points higher than that of sick elderly individuals. Conclusions: Based on these findings, elderly individuals who rely on others to perform their tasks express a lower level of dignity. Therefore, it is essential to focus on the concept of independence and develop and educate programs to maintain functional independence. These efforts can significantly improve dignity in the elderly, leading to an increase in their quality of life and satisfaction.